2023
DOI: 10.1177/23259671231176991
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Tibial Spine Avulsion Fractures After Open Reduction With Osteosuturing Versus Arthroscopic Screw Fixation: A Multicenter Comparative Study

Abstract: Background: More information is needed regarding return to preinjury sport levels and patient-reported outcomes after tibial spine avulsion (TSA) fracture, which is most common in children aged 8 to 12 years. Purpose: To analyze return to play/sport (RTP), subjective knee-specific recovery, and quality of life in patients after TSA fracture treated with open reduction with osteosuturing versus arthroscopic reduction with internal screw fixation. Study Design: Cohort study; Level of evidence, 3. Methods: This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…Twelve studies reported outcomes with the use of sutures only, of which nine studies used ARIF [ 11 , 13 , 16 , 31 , 32 , 37 , 45 , 46 , 48 ], and three studies used both ARIF and ORIF [ 17 , 19 , 38 ]. Four studies directly compared the use of sutures with the use of screws [ 12 , 14 , 22 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies reported outcomes with the use of sutures only, of which nine studies used ARIF [ 11 , 13 , 16 , 31 , 32 , 37 , 45 , 46 , 48 ], and three studies used both ARIF and ORIF [ 17 , 19 , 38 ]. Four studies directly compared the use of sutures with the use of screws [ 12 , 14 , 22 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…A representation of this can be seen in Figure 4. After pooling the outcomes of the studies comparing screw and suture interventions [12,22], the results revealed a significantly increased risk of screw fixation over suture fixation for post-operative pain (OR [95% CI] = 28.75 [2.45, 337.10], p = 0.007). A representation of this can be seen in Figure 4.…”
Section: Screw Vs Suture Risk Of Post-operative Painmentioning
confidence: 99%
See 1 more Smart Citation
“…ORIF demonstrated a higher Lysholm score compared to the ARIF technique. Indeed, as Jääskelä et al showed, children who underwent open surgery for TEF usually have a quicker return to play/sports [ 34 ].…”
Section: Discussionmentioning
confidence: 99%